A neural tract tracing study on synaptic connections for cortical glutamatergic terminals and cervical spinal calretinin neurons in rats - Huang, Ziyun; Sun, Liping; Zheng, Xuefeng; Zhang, Ye; Zhu, Yaxi; Chen, Tao; Chen, Zhi; Ja, Linju; OuYang, Lisi; Zhu, Yaofeng; Chen, Si; Lei, Wanlong (Frontiers in Neural Circuits, 2023)
The cerebral cortex innervates motor neurons in anterior horn of spinal cord by regulation of interneurons. At present, the techniques of nerve tracing, immunohistochemistry and immunoelectron microscopy were used to explore and confirm the characteristics of synaptic connections between the corticospinal tract (CST) and the cervical spinal calretinin (Cr) interneurons. Our morphological results revealed that 1) Biotinylated dextran amine labeled (BDA+) fibers form cerebral cortex primarily presented a contralateral spinal distribution, with denser distribution in the ventral horn (VH) than in the dorsal horn (DH). It was observed under an electron microscope (EM) that BDA+ terminals formed asymmetric synapses with spinal neurons, and their mean labeling rate was no different between the DH and VH. 2) Cr immunoreactive (Cr+) neurons were unevenly distributed throughout the spinal gray matter, and were denser and larger in the VH than in the DH. At the single labeling electron microscope (EM) level, the labeling rate of Cr+ dendrites were higher in the VH than in the DH, which Cr+ dendrites mainly received asymmetric synaptic inputs, and between VH and DH. 3) Immunofluorescence triple labeling showed obvious apposition points among BDA+ terminals, synaptophysin and Cr+ dendrites, with a higher density in the VH than in the DH. 4) Double labeling in EM, BDA+ terminals and Cr+ dendrites presented the same pattern, BDA+ terminals formed asymmetric synapses either with Cr+ dendrites or Cr negative (Cr-) dendrites, while Cr+ dendrites received either BDA+ terminals or BDA- synaptic inputs. The average percentage of BDA+ terminals targeting Cr+ dendrites was higher in the VH than in the DH, but the percentage for BDA+ terminals targeting Cr- dendrites was prominently higher than targeting Cr+ dendrites, there was no difference for these BDA+ terminal size. The percentage rate for Cr+ dendrites receiving BDA+ terminal inputs was apparently less than that receiving BDA- terminal inputs, and the BDA+ terminal size was larger than the BDA- terminal size received by Cr+ dendrites. The present morphological results suggested that spinal Cr+ interneurons involved in the regulatory process of the cortico-spinal pathway.